Coronary Angiography After Transcatheter Aortic Valve Replacement (TAVR) to Evaluate the Risk of Coronary Access Impairment After TAVR‐in‐TAVR. Issue 13 (7th July 2020) - Nai Fovino, Luca; Scotti, Andrea; Massussi, Mauro; Cardaioli, Francesco; Rodinò, Giulio; Matsuda, Yuji; Pavei, Andrea; Masiero, Giulia; Napodano, Massimo; Fraccaro, Chiara; Fabris, Tommaso; Tarantini, Giuseppe
Abstract : Background: Transcatheter aortic valve replacement (TAVR)‐in‐TAVR is a possible treatment for transcatheter heart valve (THV) degeneration. However, the displaced leaflets of the first THV will create a risk plane (RP) under which the passage of a coronary catheter will be impossible. The aim of our study was to evaluate the potential risk of impaired coronary access (CA) after TAVR‐in‐TAVR. Methods and Results: We prospectively performed coronary angiography after TAVR with different THVs in 137 consecutive patients, looking where the catheter crossed the valve frame. If coronary cannulation was achieved from below the RP, the distance between valve frame and aortic wall was measured by aortic angiography. CA after TAVR‐in‐TAVR was defined as feasible if the catheter passed above the RP, as theoretically feasible if passed under the RP with valve‐to‐aorta distance >2 mm, and as unfeasible if passed under the RP with valve‐to‐aorta distance ≤2 mm. Seventy‐two patients (53%) received a Sapien 3 THV, 26 (19%) received an Evolut Pro/R THV, and 39 (28%) received an Acurate Neo THV. CA after TAVR‐in‐TAVR was considered feasible in 40.9% (68.1%, 19.2%, and 5.1%, respectively; P <0.001), theoretically feasible in 27.7% (8.3%, 42.3%, and 53.8%, respectively; P <0.001), and unfeasible in 31.4% (23.6%, 38.5%, and 41.1%, respectively; P =0.116). Independent predictors of impaired CA after TAVR‐in‐TAVR were female sex (odds ratio [OR], 3.99; 95% CI, 1.07–14.86; P =0.040), sinotubular junction diameter (OR, 0.62; 95% CI, 0.48–0.80; P <0.001), and implantation of a supra‐annular THV (OR, 6.61; 95% CI, 1.98–22.03; P =0.002). Conclusions: CA after TAVR‐in‐TAVR might be unfeasible in >30% of patients currently treated with TAVR. Patients with a small sinotubular junction and those who received a supra‐annular THV are at highest risk of potential CA impairment with TAVR‐in‐TAVR.